2017
DOI: 10.4236/ojss.2017.711024
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Vegetables Farming and Farmer’s Perception of Soil and Water Degradation in Two Periurban Areas in Yaounde Cameroon

Abstract: Vegetable farming is an activity sensitive to the dynamism of the population and to the level of intensification in the use of soil resources. A study was conducted in the peri-urban zones of Yaoundé to present the socioeconomic characteristics of vegetable farming and the farmers' perception of soil and water degradation as a result of this activity. A semi-structured questionnaire was administered to this purpose in 2016 in two vegetable farming sites in Yaoundé, namely Nkolbisson and Nkolondom III. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 5 publications
(5 reference statements)
0
10
0
3
Order By: Relevance
“…Improper use of insecticides in agriculture and public health has been recognized as a major factor leading to the selection of insecticide resistance in malaria vectors, with substantial temporal variations as a function of treatment cycles and seasonality [4][5][6][7][8][9]. Considering the likely selection pressure, which is continuously imposed on the malaria vector populations due to heavy use of insecticides in market gardening areas [32], the observed resistance pattern does not come as a surprise. Indeed, swamps in Yaoundé are subject to urban agriculture permanently operating throughout the year with intensive and improper use of chemical insecticides [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Improper use of insecticides in agriculture and public health has been recognized as a major factor leading to the selection of insecticide resistance in malaria vectors, with substantial temporal variations as a function of treatment cycles and seasonality [4][5][6][7][8][9]. Considering the likely selection pressure, which is continuously imposed on the malaria vector populations due to heavy use of insecticides in market gardening areas [32], the observed resistance pattern does not come as a surprise. Indeed, swamps in Yaoundé are subject to urban agriculture permanently operating throughout the year with intensive and improper use of chemical insecticides [24].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, swamps in Yaoundé are subject to urban agriculture permanently operating throughout the year with intensive and improper use of chemical insecticides [24]. Previous studies revealed that agricultural pesticides and mainly insecticide applications are commonly utilized in Nkolondom and Nkolbisson, although the farmers do not receive specific training on pesticide management [32]. Indeed, insecticides of different classes, including pyrethroids (cypermethrin, deltamethrin, and lambdacyhalothrin), carbamates (carbofuran), organophosphates (Dimethoate, Diazinon, and Pyriforce ® (chlorpyrifos ethyl)), and organochlorines (Endosulfan), are frequently used by farmers to fight against crop pests in vegetable farms in Yaoundé [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yaoundé has an exceptionally dense hydrologic network comprised mainly of the Mfoundi river and its perennial affluent. The soil in the lowlands is hydromorphic with a mixture of fine sand and organic material in decomposition [19].…”
Section: Study Areamentioning
confidence: 99%
“…With this mind-set, they apply all these toxic agricultural chemicals in order to improve crop yields which they can sell and make more money. Studies carried out by some researchers (Manfo et al, 2019;Mfopou et al, 2017;Asanga-Fai et al, 2019;Tarla et al, 2013;Tarla et al, 2014;Yengoh and Ardo, 2014;Tarla et al, 2015;Nkemleke, 2019;Tarla et al, 2020;Yengoh and Ardo, 2014;Tarla et al, 2015;Nkemleke, 2019;Tarla et al, 2020) have generally shown that most of the farmers involved in market gardening, apply a lot of toxic agricultural chemicals in order to improve crop productivity and increase farm income.…”
Section: Toxic Agricultural Chemicals Used By Agroforestry and Non-agroforestry Practicing Farmersmentioning
confidence: 99%